Hubungan Citra Tubuh dengan Status Gizi pada Mahasiswi Program Studi Pendidikan Dokter Fakultas Kedokteran Universitas Lampung - Marzon, Mafalda; Zuraida, Reni; Oktafany, Oktafany; Berawi, Khairun Nisa (Medula, 2024)
In adolescence, health and nutrition have an important role in determining health and nutritional status in the next phase of the life cycle. The prevalence of abnormal nutritional status in Lampung Province is 24.91% for late adolescence aged 19 years and 35.97% for aged 20-24 years, while normal nutritional status for those aged 19 years is 75.09% and those aged 20-24 year amounted to 64.03% according to Riskesdas 2018. This occurs because there are factors that can influence nutritional status, such as body image. This study aims to determine the relationship between body image and nutritional status. The research design used in this research is analytical with a cross sectional approach, with a simple random sampling technique. There were 116 respondents obtained using the unpaired comparative categorical analytical formula. In this study there were 2 variables, namely body image and nutritional status. Body image variables are measured by MBSRQ (Multidimensional Body Self Relations Questionnaire) and body image variables are measured by body mass index. The data collected was analyzed univariately and bivariately with Chi-Square. The results of the univariate test showed that abnormal nutritional status was 65.5%, while normal nutritional status was 34.5%. In terms of body image, 20.7% of respondents had a positive body image and 79.3% had a negative body image. Based on bivariate analysis, there is a relationship between body image and nutritional status (p = 0.023). From the research results, it can be concluded that there is a significant relationship between body image and the nutritional status of students in the Medical Education Study Program, Faculty of Medicine, University of Lampung.